Out-of-time-order correlators of nonlocal block-spin and random observables in integrable and nonintegrable spin chains - Shukla, Rohit Kumar; Lakshminarayan, Arul; Mishra, Sunil Kumar (American Physical Society, 2022)
Out-of-time-order correlators (OTOC) in the Ising Floquet system, which can be both integrable and nonintegrable, are studied. Instead of localized spin observables, we study contiguous symmetric blocks of spins or random operators localized on these blocks as observables. We find only power-law growth of OTOC in both integrable and nonintegrable regimes. In the nonintegrable regime, beyond the scrambling time, there is an exponential saturation of the OTOC to values consistent with random matrix theory. This motivates the use of "prescrambled"random block operators as observables. A pure exponential saturation of OTOC in both integrable and nonintegrable system is observed, without a scrambling phase. Averaging over random observables from the Gaussian unitary ensemble, the OTOC is found to be exactly same as the operator entanglement entropy, whose exponential saturation has been observed in previous studies of such spin chains.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Correlators; Quantum entanglement; Spin dynamics; Block-spin; Exponentials; Floquet systems; Localized spin; Nonlocal; Spin chains; Spin observables; Spin operators; Symmetrics; Time ordering; Random variables